Characterization of an azo-dye-degrading white rot fungus isolated from Malaysia - Cheng, W. N.; Sim, H. K.; Ahmad, Siti Aqlima; Syed, Mohd. Arif; Abd Shukor, Mohd Yunus; Yusof, Mohd. Termizi (Guizhou Academy of Agricultural Sciences, 2016)
Sixty-three local white-rot fungi were isolated from soil and wood samples on potato dextrose agar (PDA). All these isolates were screened for their ability to degrade 4 textile azo dyes;Ponceau 2R (C.I. 16450), Orange G (C.I. 16230), Direct Blue 71 (C.I. 34140) and Biebrich Scarlet (C.I. 26905). Out of 40 isolates that gave positive results, only 1 promising isolate which completely degrades all 4 dyes in the minimum amount of time was selected for further investigation. This isolate was sourced from University Putra Malaysia (UPM) Serdang campus.The isolate was tentatively identified as Coriolopsis sp. Strain arf5 based on the analysis of the internal transcribed spacer (ITS) region. Nutritional studies on defined solid medium showed that this isolate was only able to degrade the 4 azo dyes under nitrogen-limiting conditions and an additional carbon source (glucose) need to be added to provide sufficient energy for the degradation to occur. Various parameters were optimized.